"In Sweden we shake hands" - but are we really (Sociologisk Forskning, 2017)
Motivated by a recent controversy over handshaking, a survey of the personal networks of young Swedes (n=2244) is used to describe greeting practices across social class, gender, immigrant background, and geographic location. While greeting practices in the sample are fairly uniform, there are also important differences. Handshaking is predominantly used by respondents with an immigrant background, men and women distinguish between greetings depending on the gender of the person they are greeting, and greeting practices differ between northern and southern Sweden as well as between rural and urban areas.